Racial Disparities in Cardiovascular Health Behaviors: The Coronary Artery Risk Development in Young Adults Study - Whitaker, Kara M. (Am J Prev Med, 2018)
INTRODUCTION: There are known racial differences in cardiovascular health behaviors, including smoking, physical activity, and diet quality. A better understanding of these differences may help identify intervention targets for reducing cardiovascular disease disparities. This study examined whether socioeconomic, psychosocial, and neighborhood environmental factors, in isolation or together, mediate racial differences in health behaviors. METHODS: Participants were 3,081 men and women from the Coronary Artery Risk Development in Young Adults study who were enrolled in 1985–1986 (Year 0) and completed a follow-up examination in 2015–2016 (Year 30). A health behavior score was created at Years 0, 7, 20, and 30 using smoking, physical activity, and diet assessed that year. The race difference in health behavior score was estimated using linear regression in serial cross-sectional analyses. Mediation analyses computed the proportion of the race and health behavior score association attributable to socioeconomic, psychosocial, and neighborhood factors. RESULTS: Data analysis conducted in 2016–2017 found that blacks had significantly lower health behavior scores than whites across 30 years of follow-up. Individual socioeconomic factors mediated 48.9%–70.1% of the association between race and health behavior score, psychosocial factors 20.3%–30.0%, and neighborhood factors 22.1%–41.4% (p<0.01 for all). CONCLUSIONS: Racial differences in health behavior scores appear to be mediated predominately by correspondingly large differences in socioeconomic factors. This study highlights the profound impact of socioeconomic factors, which are mostly not under an individual’s control, on health behaviors. Policy action targeting socioeconomic factors may help reduce disparities in health behaviors.